SARS-CoV-2 and community-acquired pneumonia leading to euglycemic diabetic ketoacidosis in two patients with type-1 diabetes mellitus who were not using SGLT2 inhibitors - Telci Çaklılı, Özge; Gürbüz, Hande (Journal of Surgery and Medicine, 2022)
Diabetic patients are at high risk for mortality after contracting several infections. Additionally, diabetes has been mentioned as an independent factor for progression to severe disease in seasonal influenza and in-hospital deaths due to coronavirus 2019 (COVID-19). Diabetic ketoacidosis is a well-known complication of type-1 diabetes and is characterized by hyperglycemia, metabolic acidosis, and high ketone levels. Euglycemic diabetic ketoacidosis (EDK) is a rare variant of diabetic ketoacidosis in which the blood glucose levels remain within normal limits, but ketoacidosis develops. Although EDK has often been associated with the use of sodium–glucose transport-2 (SGLT-2) inhibitors, it can be induced by several factors, including infectious diseases. EDK may present during the course of an infection, and it also can be a manifestation indicating infection. In this report, two cases of EDK due to pneumonia caused by two different pathogens are presented. Moreover, it is important to emphasize that EDK can occur in type-1 diabetic patients who are not using SGLT-2 inhibitors. Additionally, EDK can be a manifestation of infection and a possible marker of progression to severe disease in patients with type 1 diabetes.